Quality of pediatric anesthesia: A cross-sectional study of a university hospital in a low-income country. - Oskar Andersson; Peter Radell; Victor Ringo; Moses Mulungu; Tim Baker (PLoS ONE, 2018)
To evaluate the quality of pediatric anesthesia in a university hospital in Dar es Salaam, Tanzania.A cross-sectional study conducted using a new tool that was developed from the literature and WHO recommendations including 28 parameters as standards for pediatric anesthesia. These 28 parameters consisted of 17 structure parameters of the equipment and medicines that should be present in theatre before any surgery starts, and 11 process parameters of actions taken by staff. Adverse events occurring during the anesthesia were recorded.30 patients were included, aged between 1.5 months to 5 years with a mean of 2.4 years. 26 of the patients underwent elective surgery and 4 patients emergency surgery. Nine parameters were always present and one parameter (bag and mask) was not available for any of the patients. The structure index ranged from 71% to 94% with a mean of 84%. The process index had a mean score of 71% with a range from 50% to 90%: lower than the structure index (p<0.001). With the structure and process index combined the average score was 79% with a low of 67% and high of 89%. 70 adverse events were observed with a range from 0 to 7 adverse events per patient. The most common adverse event was hypoxia at extubation in 20 (69%) patients. Nine patients had an episode of severe hypoxia at extubation.Pediatric anesthesia in low resource settings suffers from deficiencies in the structures and processes of providing good quality care. Improvement efforts may be best focused on improving the consistency and quality of the process of care and a reduction in adverse events rather than the structures available. Use of the assessment tool developed for this research could be useful for systematic quality-improvement efforts and to assess the needs in different settings.